PENGARUH MANAJEMEN KUALITAS TERHADAP KINERJA USAHA DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL MEDIASI PADA USAHA MINUMAN BOBA DI KOTA PEKANBARU - Hamrad Hamrad; Samsir Samsir; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of quality management practices on businessperformance and business competitive advantage as a mediating variable in theboba beverage business in Pekanbaru City. The population in this study were bobabeverage businesses in Pekanbaru City, totaling 83. The sampling technique usedthe Slovin formula so that the number of research samples was 69. The hypothesistesting in this study used Structural Equation Modeling (SEM) with SmartPLS. Theresults of the study show that 1) Total quality management practices has a positiveand significant effect on competitive advantage in the Boba Beverage Business inPekanbaru City. 2) Total quality management practices has a positive andsignificant effect on business performance at the Boba Beverage Business inPekanbaru City. 3) Competitive Advantage has a positive and significant effect onbusiness performance in the Boba Beverage Business in Pekanbaru City. 4)Competitive advantage mediates the relationship between total qualitymanagement practices and business performance in the Boba Beverage Business inPekanbaru City. Keywords : Total Quality Management Practice, Business Performance,Competitive Advantage.